Assembly of vermiculite/SnO2 composite membranes with high ion selectivity for enhancing osmotic energy conversion performance - Fu, Yuyang; Chen, Zhibo; Zhang, Yating; Xie, Bichen (Frontiers in Materials, 2025)
For osmotic energy harvesting based on nanofluidic membranes, aqueous instability, less-than-optimal ion selectivity, and moderately high internal resistance can somewhat restrict its performance advancement. This study develops a novel composite membrane combining 2D SnO2 and vermiculite (VMT) nanosheets to balance permeability and ion selectivity, boosting power density. The optimized membrane achieves an output power density of 0.727 W m-2 using simulated saltwater/river water, offering a promising solution for efficient osmotic energy conversion.